The Influence of Positivism and Empirism in The Enforcement of Islamic Inheritance Law in Indonesia - Zaman, Jamrud Qomaruz; Sholeh, Achmad Khudori; Fadil, Fadil; Salam, Nor; Binti Ros Azman, Aina Sofea (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2024)
Positivism and empiricism are modern paradigms become the basic guidelines for the schools of legal philosophy, namely legal positivism and legal realism. However, the current condition in Indonesia is dominated by the paradigm of legal positivism so that everything must be by written law. The practice of inheritance division that is always based on the concept of 2:1 as in the Compilation of Islamic Law is felt to be incompatible with community justice. The purpose of this research is to enrich the study of the positivism and empiricism paradigms as a renewal of Islamic inheritance law in Indonesia. The benefit of this research is to inform that the integration of positivism and empiricism in law will produce competent law enforcement. This research is a normative research with a conceptual approach and data sources in the form of literature and data analysis techniques, namely evaluation. The results of this research are; (1) The factor that causes judges in Indonesia to use the judicial restraint approach excessively as a characteristic of legal positivism is the legal culture of the application of the civil law legal system. (2) The solution to the problem offered is to borrow Fazlur Rahman's double movement theory, namely historical contextualisation by taking universal values from the norm. Therefore, it is time for judges to be free to move to realize moral justice within the limits set by the Constitution and the Law on Judicial Power.